Inhibition of Alpha-amylase of Kratom Tea (Mitragyna speciosa Korth.) on Various Brewing Treatment - Dhayan, Rosa; Purwayantie, Sulvi; Fadly, Dzul (FoodTech: Jurnal Teknologi Pangan, 2025)
Kratom (Mitragyna speciosa Korth.) is a plant that is believed by the public capable to overcome hyperglycemia conditions in diabetics. Hyperglycemia conditions in diabetics can be controlled through inhibition of carbohydrate-breaking enzymes such as alpha-amylase. Secondary metabolites in adequate amount are expected to inhibit the action of the alpha-amylase enzyme which is a key enzyme in the digestion of complex carbohydrates. One of the ways to increase the availability of secondary metabolites so that they can activate the alpha-amylase enzyme is by steeping. This study aims to determine the effect of temperature and time of steeping in kratom tea to inhibits alpha-amylase enzyme. This study uses Randomized Block Design (RBD) with two treatment factors, consisting of 3 treatments of brewing temperature (70, 85, 100oC) and 3 treatments of brewing time (5, 10, 15 minutes), with 4 replications. The data are analyzed using ANOVA test (a=5%) and BNJ (a=5%). The parameters tested in this study consist of levels of phenolics, flavonoids, and alpha-amylase inhibition. The results show that increasing temperature and brewing time of kratom tea increased the content of phenolics and flavonoids, but the results are inversely related to the alpha-amylase inhibition. Based on the ANOVA analysis, there was no effect of temperature and steeping time on the inhibition of the alpha-amylase enzyme.